Online risk exposure and anxiety among college students in China: The chain mediating role of negative attribution and interpersonal security - Haihong Wang; Shang Zhang; Na Sun; Senqing Qi; Xinfa Yi (PLoS ONE, 2025)
Despite evidence supporting the relationship between online risk exposure and anxiety, the underlying mechanisms remain underexplored. This study aimed to construct and validate a chain-mediation structural equation model to investigate how online risk exposure influences anxiety among college students. Data was collected online in April 2023 from a sample of college students (N =  986, 64.6% female) using validated scales measuring online risk exposure, negative attribution, interpersonal security, and anxiety. The results showed that online risk exposure not only directly exacerbates anxiety but also indirectly affects it through three distinct pathways: negative attribution, interpersonal insecurity, and their chain relationship. These mediation effects accounted for 41.16%, 20.47%, and 4.65% of the total effects, respectively. These findings highlight the importance of targeted interventions aimed at reducing online risk exposure, improving negative attribution styles, and enhancing interpersonal security among college students. The study concludes by discussing its limitations and proposing directions for future research.